Új térközösségi kategóriák keresése Magyarországon a II. világháború befejezésének és az újjárendeződés megindulásának időszakában : 1944-1947 - Hajdú, Zoltán (Közép-Európai Közlemények, 2013)
At the end of the World War II the representatives of Hungarian sciences (historians, geographers, economists, cartographers etc.) were started new “objective” spatial categories (Middle Danube Basin, Central Europe, Danubelandscape, Carpatian Basin) for peoples living together between Germany and the Soviet Union. The main elements of these researches were: how to reach “independence” of these peoples and countries, and on the other hands how to garantee of interest of Hungarians in the framework of new situation. Most of the authors in there analyses and publications were „idealists”. The new rearangement of the wide territory were dominated by Soviet influences, without real independences of smaller peoples and countries.